MEDI‐551 Treatment Effectively Depletes B Cells and Reduces Serum Titers of Autoantibodies in Mice Transgenic for Sle1 and Human CD19. Issue 4 (April 2016) - Gallagher, Sandra; Yusuf, Isharat; McCaughtry, Tom M.; Turman, Sean; Sun, Hong; Kolbeck, Roland; Herbst, Ronald; Wang, Yue
Abstract : Objective: To evaluate treatment with MEDI‐551, a humanized anti‐human CD19 monoclonal antibody, in a model of autoimmunity involving mice transgenic (Tg) for Sle1 and human CD19 (hCD19). Methods: Sle1 .hCD19‐Tg mice were given either a single intravenous dose of MEDI‐551 or repeated doses of MEDI‐551 biweekly for up to 12 weeks. The numbers of B cells in the blood, spleen, and bone marrow were determined by flow cytometry assay. In the spleen and bone marrow, the number of IgM‐ and IgG‐specific antibody‐secreting cells (ASCs) and the number of ASCs specific for anti–double‐stranded DNA (anti‐dsDNA) were determined by enzyme‐linked immunospot assay. Serum autoantibody and total immunoglobulin levels were determined by enzyme‐linked immunosorbent assay, and levels of inflammatory proteins were tested using a multianalyte profiling platform. Results: MEDI‐551 treatment of Sle1 .hCD19‐Tg mice resulted in effective and sustained B cell depletion throughout the duration of the experiment. The frequency of IgM and IgG ASCs in the spleen was reduced by ≥90%, whereas in the bone marrow, the total ASC frequency was not changed. Levels of autoantibodies specific for dsDNA as well as antihistone and antinuclear antibodies were each reduced by 40–80%, but total serum immunoglobulin levels were largely unchanged at the end of 12 weeks of treatment. Conclusion: These findings highlight the ability of MEDI‐551 to deplete B cells and ASCs in autoimmune Sle1 .hCD19‐Tg mice. MEDI‐551 treatment resulted in a robust reduction of autoantibodies but had minimal effect on total serum immunoglobulins. Thus, the novel ability of MEDI‐551 to remove a broad range of B cells as well as to lower most disease‐driving autoantibodies in an autoimmune disease mouse model warrants continued research. Several clinical studies to explore the safety and activity of MEDI‐551 in autoantibody‐associated autoimmune diseases are ongoing.